Occupational Аccidents and Near-Miss Events in the Internal Medicine Services: Turkey Sample in University Hospital - Pelin Uymaz (Publishing House Zaslavsky, 2021)
Background. Health institutions are considered occupational areas with high risk due to the need for human resources, including numerous specialists with distinct characteristics, use of intensive technology, and complex occupational processes. The importance of occupational health and safety, which aims to eliminate or minimize all these negativities, is increasing rapidly. The purpose of this study is to examine the frequency of exposure to occupational accidents and near-miss events of the nurses and physicians working in the internal medicine units of a university hospital, and their reporting status and factors affecting these characteristics. Materials and methods. This research is a descriptive study, and the data of the recent year have been evaluated. The research was carried out in internal medicine units of a university hospital in Istanbul. The data in this study were collected by using the “Evaluation Form for Occupational Accidents and Near-Miss Events” which was created by the researchers. Results. A total of 117 individuals, 83 women (70.94 %), and 34 men (29.06 %) participated in this study. Of the participants, 59 were nurses (50.43 %), and 58 were physicians (49.57 %). There was a significant moderate positive correlation (r = 0.305) between age and the number of occupational accidents (p = 0.039). The average number of occupational accidents experienced by nurses (1.31 ± 0.74) was found to be lower than physicians (2.80 ± 2.53) (p = 0.006). The number of near-miss incidents experienced by physicians (2.79 ± 4.30) was higher than the nurses (1.29 ± 83.00) (p = 0.032). Conclusions. Every workplace accident or near-miss event experienced by healthcare professionals should be reported and analyzed carefully to prevent future workplace accidents. Training of health professionals on health risks they may encounter and protective measures against occupational accidents have vital importance.